2015
DOI: 10.1038/srep11283
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Eating Phenotype is Associated with Central Dopamine D2 Receptor Binding Independent of Body Mass Index

Abstract: PET studies have provided mixed evidence regarding central D2/D3 dopamine receptor binding and its relationship with obesity as measured by body mass index (BMI). Other aspects of obesity may be more tightly coupled to the dopaminergic system. We characterized obesity-associated behaviors and determined if these related to central D2 receptor (D2R) specific binding independent of BMI. Twenty-two obese and 17 normal-weight participants completed eating- and reward-related questionnaires and underwent PET scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 55 publications
4
37
1
Order By: Relevance
“…However, the association between obesity and the DR remains unclear as the result of lack of agreement among previous studies. A lower availability of DR in obese individuals than in non‐obese individuals was reported for the first time by Wang et al However, the opposite was also observed, as well as the absence of a difference in availability of DR between obese and non‐obese individuals . This inconsistency could be attributed to the characteristics of the radiopharmaceuticals.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the association between obesity and the DR remains unclear as the result of lack of agreement among previous studies. A lower availability of DR in obese individuals than in non‐obese individuals was reported for the first time by Wang et al However, the opposite was also observed, as well as the absence of a difference in availability of DR between obese and non‐obese individuals . This inconsistency could be attributed to the characteristics of the radiopharmaceuticals.…”
Section: Discussionmentioning
confidence: 89%
“…A lower availability of DR in obese individuals than in nonobese individuals was reported for the first time by Wang et al 6 However, the opposite was also observed, as well as the absence of a difference in availability of DR between obese and non-obese individuals. 26,27 This inconsistency could be attributed to the characteristics of the radiopharmaceuticals. For example, in individuals who were scanned with both 11 C-PHNO and 11 C-raclopride, different associations between the radiopharmaceuticals and obesity were found, even in the same individual.…”
Section: Discussionmentioning
confidence: 99%
“…Data from these individuals regarding the relationship between obesity and striatal D2R were previously presented (Eisenstein et al, 2013; Eisenstein et al, 2015b; Eisenstein et al, 2015a). Obese ( n = 24) and non-obese ( n = 20) individuals, aged 18-40 years, were eligible for the study based on strict inclusion and exclusion criteria (Eisenstein et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…There are consistent findings in the animal literature that HFD, and adiposity alter DA signaling at the cellular, and molecular levels (Anderzhanova et al, 2007; Johnson and Kenny, 2010; van de Giessen et al, 2012, 2013; Sharma and Fulton, 2013; Tellez et al, 2013; Cansell et al, 2014; Adams et al, 2015; Woods et al, 2016), as well as mounting evidence for altered DA signaling in human obesity, especially reflected in changes in DA receptor density, (Wang et al, 2001, 2011; Dunn et al, 2010; Steele et al, 2010; Eisenstein et al, 2013, 2015; Guo et al, 2014; Cosgrove et al, 2015; Horstmann et al, 2015; Karlsson et al, 2015; Caravaggio et al, 2015b; Dang et al, 2016; Gaiser et al, 2016). Additionally, there is evidence that central and peripheral insulin resistance might impact DA function.…”
Section: Neurocognitive Deficits May Be Domain-specific and Differentmentioning
confidence: 99%